Apical Variant of Hypertrophic Cardiomyopathy Presenting as Recurrent Syncope and Wide Complex Tachycardia - Paudel, Navaraj; Alurkar, V.M.; Jha, G.S.; Kafle, Ramchandra; Sapkota, Subash; Dhakal, Niraj (Journal of Advances in Internal Medicine, 2017)
Apical hypertrophic cardiomyopathy (AHC) is an uncommon variant of hypertrophic cardiomyopathy usually found as an incidental finding during routine echocardiography. It was first described by Sakamoto in 1976 in Japanese patients. Echocardiography is still considered as the best screening tool to assess AHC although MRI is considered as the gold standard for confirmation. In this case, we present a 21-year-old man with AHC who presented with recurrent brief syncopal episodes which were ignored by the patient until he was brought to us with prolonged syncope and wide complex tachycardia/ posterior fascicular ventricular tachycardia. We observed the classical findings in the plain twelve lead electrocardiograms done after cardioversion. It is always wise to keep special attention to evaluate hypertrophic cardiomyopathy (HCM) in young patients presenting with syncope. Journal of Advances in Internal Medicine 2017;06(02):32-34.